Itinerários de Ludvig Gideon Kumlien e a (re)produção da ginástica sueca (1895-1921) - Iara Marina dos Anjos Bonifácio (2019)
This research focuses on examining the role played by Ludvig Kumlien (1874-1934) in (re)production the Swedish Gymnastics. This aims research problematize the active role of individuals in the creation of ways of practicing Swedish Gymnastics over time. Originally from Eskilstuna, Sweden, he moved to Paris, France, in 1895 and, once there, he performed different actions towards promoting the Swedish Gymnastics, e.g. organizing gymnastics demonstrations, creating an Institute, and publishing manuals. His initiatives were part of a movement launched by the Royal Central Institute of Gymnastics (GCI) and the Swedish crown, which mainly focused on migration in order to promote the Swedish Gymnastics. This systematization proposed by Pier Henrik Ling (1776-1839) intended to develop harmonically-built bodies based on scientific beliefs – a practical and rational method –, by means of symmetrical and precise movements. Its creation process proceeded along the two first decades of the 19th century, when Ling became director of the GCI in 1813, place where individuals were educated and became qualified to teach Swedish Gymnastics in Sweden. The creation of this systematization relates to a discussion that had been highlighting the need to create an educational system that included physical education since the end of the 18th century in Europe. By examining the literature, it is possible to notice that is potential in examining the process of circulation of this cultural object – the Swedish Gymnastics – by means of examining the subjects involved and their routes. In order to do so, the sources analyzed were the manuals, newspapers, magazines, and his family book, available in physical and digital archives. As the theoretical and methodological framework, the notions of circulation, sociability and mediating intellectuals were adopted in an attempt to understand the role played by Ludvig Kumlien. They revealed the strategies devised, the relations established, the places occupied, and the courses of actions that allowed his (re)produced ideas about the Swedish Gymnastics to circulate, mainly through manuals in different countries and languages, and that somehow contributed to the conformation of physical education in those places. We observed that Ludvig Kumlien transformed the Swedish Gymnastics by promoting it when bringing it in contact with another culture, between acceptance and resistance, thus developing his own Swedish Gymnastics. In this process, he takes on different roles, as either teacher or promoter, and broadcasts his gymnastics through different languages.